2018
DOI: 10.4038/sljfa.v4i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Spatial linkages of green chili prices between a dedicated economic centre and other regional markets in Sri Lanka

Abstract: This study assesses the green chili markets in Sri Lanka from 2012 to 2016 by examining the degree of market integration in the country. The analysis was carried out in the first differenced form, which conformed to the Augmented Dickey-Fuller tests of stationary. The pairwise comparison between Dambulla Dedicated Economic Centre (DDEC) and 25 other regional markets in Sri Lanka was carried out. All market pairs co-integrated with the price at DDEC in the long run according to the results of Johansen Co-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A study conducted by Jayasinghe-Mudalige (2006) on spatial integration of regional rice markets in Sri Lanka suggested that the prices in several selected rice markets were highly integrated both in the short-run and long-run perspectives. Another study by Thamiem et al (2010), on market integration of Sri Lankan milk market revealed that the prices of central milk markets in the country significantly influence the price levels in the neighbouring regional markets while transmitting to the regional markets at a degree of 0.24 to 1.02 within a geographical region. De Silva (2006) examined price efficiency in tuna fish marketing in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Jayasinghe-Mudalige (2006) on spatial integration of regional rice markets in Sri Lanka suggested that the prices in several selected rice markets were highly integrated both in the short-run and long-run perspectives. Another study by Thamiem et al (2010), on market integration of Sri Lankan milk market revealed that the prices of central milk markets in the country significantly influence the price levels in the neighbouring regional markets while transmitting to the regional markets at a degree of 0.24 to 1.02 within a geographical region. De Silva (2006) examined price efficiency in tuna fish marketing in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Findings revealed that all the tuna fish markets were integrated and showed short-run stability and were somewhat competitive. To the best of the authors' knowledge, only Sandaruwani (2018) examined the spatial integration of vegetable markets in Sri Lanka. Her findings showed that only six regional markets for green chili, out of the 25 markets examined, were integrated with DDEC.…”
Section: Introductionmentioning
confidence: 99%